Production and use of spheroids at the Early Palaeolithic in Europe and Africa : comparative and integrative approach of enigmatic and emblematic artefacts - (:unkn) unknown (My University, 2023)
Polyhedrons, spheroids and bolas (PSBs) are enigmatic stone objects ranging from cubic to spherical shapes, present in archaeological records for two million years. They stand among the oldest stone artefacts manufactured by hominins, and their functions remain poorly understood. Interestingly, PSBs are quite common in Africa and Asia but rare in Europe.The aims of this thesis are to gain a better understanding of the production and use modes of these objects and to explore the reasons for their scarcity in Europe. These issues were addressed through a comprehensive and integrative study combining archaeological data (technological, wear and metric analysis of a corpus of 513 PSBs from nine assemblages in Europe and North Africa, dated between 1.78 and 0.169 Ma), experimental studies and ethno-historical insights.As a result, an original reference of experimental traces was constructed, comprising nearly 50,000 photographs of macro and micro-traces related to the production and use of PSBs in various activities. Combining this reference with the wear-study of the corpus allowed for the creation of an identification key for potential functions of PSBs on a case-by-case basis. PSBs could have had various functions, even multiple functions according to the pieces. For example, some could have been used in percussive activities (active, passive) and/or served as cores. “Hard” rocks were systematically selected to produce PSBs, likely for tasks requiring resistance in heavy-duty tasks. Flint was consistently avoided worldwide. The scarcity of PSBs in Northwestern Europe could be a result of a combination of environmental, cultural and functional factors : the abundance of flint in the environment may have orientated lithic production towards the exploitation of siliceous rocks (both as an environment adaptation and a choice since other materials were also available), resulting in predominantly flint assemblages where PSBs are missing, given that flint
Keywords: African Research